2016
DOI: 10.1007/s40273-016-0389-9
|View full text |Cite
|
Sign up to set email alerts
|

Health, Health-Related Quality of Life, and Quality of Life: What is the Difference?

Abstract: The terms health, health-related quality of life (HRQoL), and quality of life (QoL) are often used interchangeably. Given that these are three key terms in the literature, their appropriate and clear use is important. This paper reviews the history and definitions of the terms and considers how the terms have been used. It is argued that the definitions of HRQoL in the literature are problematic because some definitions fail to distinguish between HRQoL and health or between HRQoL and QoL. Many so-called HRQoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
765
0
59

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,066 publications
(922 citation statements)
references
References 46 publications
2
765
0
59
Order By: Relevance
“…Furthermore, one individual screened all of the abstracts, rather than two independent reviewers, with input from additional authors to resolve questionable cases. Finally, HRQoL as a construct lacks uniform definition and the assessment of HRQoL among brain tumor patients and interpretation of HRQoL data poses unique challenges, such as the timing of the assessments, selection bias, and missing data (see Dirven et al for review). This review focused on HRQoL; however, there may be additional outcomes, such as activities of daily living, that are important and relevant to patients with brain tumors and that are not fully captured by HRQoL measures, and these should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one individual screened all of the abstracts, rather than two independent reviewers, with input from additional authors to resolve questionable cases. Finally, HRQoL as a construct lacks uniform definition and the assessment of HRQoL among brain tumor patients and interpretation of HRQoL data poses unique challenges, such as the timing of the assessments, selection bias, and missing data (see Dirven et al for review). This review focused on HRQoL; however, there may be additional outcomes, such as activities of daily living, that are important and relevant to patients with brain tumors and that are not fully captured by HRQoL measures, and these should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…It was not originally intended to be a comprehensive, standalone instrument for capturing all aspects of health for all purposes, but rather, a brief and convenient measure to be used in conjunction with other, more detailed generic and condition-specific measures [5]; though increasingly it is used as a standalone measure [6]. It should be noted that while early studies of EQ-5D referred to it as a measure of health-related quality of life, we follow the suggestion by Karimi and Brazier [7] that it is more appropriate to think of such instruments as measures of "self-perceived health status".…”
Section: Introductionmentioning
confidence: 99%
“…7,9 A recent systematic review by Quinn et al 11 of 35 studies revealed that AYA patients with cancer are more likely to have poorer quality of life (QOL) compared with the age-matched general population. 14 Although there are different definitions of QOL, 15,16 life satisfaction (LS) is a concept strongly related to QOL. However, to the best of our knowledge, only a few studies to date have investigated changes in QOL among AYA patients with cancer over time.…”
Section: Introductionmentioning
confidence: 99%